A contribuição da Língua Brasileira de Sinais para a comunicação entre surdo e família - CORREA, Renata Borges (2019)
This work aims to show how communication occurs in the family of the deaf subject within and verify how the Libras has been used in the home environment with the deaf person. So we aim to understand how the family communicates with the deaf person on a day-day; check how the Libras has been used in the home environment with the deaf person; discuss the sign language of the contribution in the family environment for the development of deaf person. The chosen type of research was qualitative, that being at first made observations with relatives and in a second stage, we conducted interviews with structured script (questionnaire) based on a schedule of activities. The survey was conducted with the residents of São Miguel do Guamá / PA, who live in two of the main streets of this city. In this study we show the means of communic ation between the families of the deaf subject to communication between them and how Libras has been used by the family, since it is the main tool for a good relationship between deaf and family. In addition, we discuss the learning process of the deaf subject, if the Libras helps or not the learning of it, and the role of family and school in this process.